"It's Back! My Remission Is Over": Online Communication of Disease Progression Among Adolescents With Cancer. (May 2016) - Keim-Malpass, Jessica; Stegenga, Kristin; Loudin, Beth; Kennedy, Christine; Kools, Susan
Cancer in adolescence presents unique challenges to patients and families due to the dramatic physical and psychological vulnerabilities that occur during a time of identity development. Additionally, adolescents who experience progression of their cancer, or failure of first-line therapies, represent an understudied group within pediatric oncology. Illness blogs offer a unique opportunity to understand the experience of a chronic or serious illness through a naturalistic and longitudinal perspective that is inherently patient centered. The purpose of this exploratory qualitative study was to describe the experiences of adolescents with cancer who experienced disease progression through analysis of their online illness blogs. Seven illness blogs written by adolescents with cancer diagnosed between the ages of 13 and 18 years were analyzed using thematic analysis. Several key themes were described among the adolescents, including normalizing the news, facing treatment failure, and reconciling chronos—the finite concept of time. These findings provide vital descriptive evidence for the experience of disease progression as described by adolescents, as well as identifying key points of further study and intervention development for nurse researchers and nurses who care for this vulnerable patient population.